If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(c + -1) = 6(b + 2) + -1a Reorder the terms: 9(-1 + c) = 6(b + 2) + -1a (-1 * 9 + c * 9) = 6(b + 2) + -1a (-9 + 9c) = 6(b + 2) + -1a Reorder the terms: -9 + 9c = 6(2 + b) + -1a -9 + 9c = (2 * 6 + b * 6) + -1a -9 + 9c = (12 + 6b) + -1a Reorder the terms: -9 + 9c = 12 + -1a + 6b Solving -9 + 9c = 12 + -1a + 6b Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 9c = 12 + -1a + 9 + 6b Combine like terms: -9 + 9 = 0 0 + 9c = 12 + -1a + 9 + 6b 9c = 12 + -1a + 9 + 6b Reorder the terms: 9c = 12 + 9 + -1a + 6b Combine like terms: 12 + 9 = 21 9c = 21 + -1a + 6b Divide each side by '9'. c = 2.333333333 + -0.1111111111a + 0.6666666667b Simplifying c = 2.333333333 + -0.1111111111a + 0.6666666667b
| 77.94-5.8+201.681= | | 2x^2-36x+162=32 | | 10a^2-27ab+5b= | | 9(n-1)=6(n+2) | | x-7=3x | | 3(x+4)=(3x+12) | | 9x-1(4x-1)=2 | | 9x+3(-3x-5)=-12-3x | | 8x-7-7x-7=8x-7x-17 | | -7b+4+5b=-3b+9 | | 2(4x+7)=3+2x+2 | | 4x^2+2x-6= | | (5y-1)(23y-1)= | | 5x^2=27 | | x^2+3x^2=x^2 | | -11x+9=-12+13 | | 6x-8=3x | | 1x-9= | | 4x-y=-10 | | t(t-2)-3t(t-2)=0 | | t(t-2)-3t(t-3)=0 | | 6(-x+4)=9 | | -2(5y+1)=4(y+6)-2 | | h=-16t^2+68t | | 5y+5=2y+10 | | 64=2(5x+2)+(3x-2) | | 2a^2-81=0 | | 1x+3x+-18x=0 | | 5x=2-2x | | x-3x+-18x=0 | | -4x^2+3x=1 | | 3(h)+6=2(h)-14 |